Organizational communication as a means to a company’s success (2022)
How can a company benefit from having active, happy and participant employees? Based on the presented analysis and theories we can conclude that organizational communication and spaces of leisure in a company, specially one constituted by thousands of young people, are major key points to achieving superb results. A proper organization becomes an important topic in managing nonverbal and verbal communication interactions amongst employees and their superiors. Maintaining a strong relationship and sense of trust between leaders and their subordinates, will have a very positive role in shaping employee motivation, satisfaction and effectiveness considering the employee will have spaces to share their opinions, make sure the employer is kept up to date with ongoing issues and explore possible measures to keep a healthy work environment and help the company grow significantly.